Padėties darbo rinkoje pokyčiai,užimtumo ir nedarbo rodiklių taikymo metodiniai ypatumai - Pocius, Arūnas (Lietuvos statistikos darbai, 2010)
The aim of the article is to reveal the main trends in the national labour market. The main focus of the analysis is on the employment and unemployment rates, used in official statistics. In the paper, certain methodological aspects of the application of key labour market indicators are highlighted, the peculiarities of the development of employment statistics are reviewed, and the structure of potential human resources and its development opportunities are assessed. This article is more closely linked with official statistics, and the priority is given to the data of Statistic Lithuania; however, the author also makes use of the Lithuanian Labour Exchange and State Social Insurance Fund Board (Sodra) data, which in their own way complement and substantiate the results of the analysis provided in the article.